Unlocking Chickpea Potential: Zinc and Iron Foliar Treatments for Enhanced Growth and Yield (Plant Bulletin, 2023)
Chickpea is one of the most important crops of Pakistan. In the current study, the effect of five doses of zinc and iron was investigated on the growth and yield of chickpeas. The treatments include basal dose of 33% ZnSO4@25kg/ha, basal dose of 33% ZnSO4 @50kg/ha, foliar application of Zn @1% solution, foliar application of Zn @ 2% solution for zinc while the iron treatments were basal dose of FeSO4 @25kg/ha, basal dose of FeSO4 @50kg/ha, foliar application of Fe @1% solution, foliar application of Fe @ 2% solution. The experiments were conducted during two growing seasons 2022 and 2023. The results indicated that foliar application of 2% zinc resulted in higher plant height (50.77-50.96 cm), more numbers of branches (16.16-16.18), pods per plant (16.71-16.92), numbers of grains per pod (1.81-1.85) and yield (1466.1-1475.5 kg per ha) compared to control and other treatments. Similarly, foliar application of 1% iron caused a significant increase in plant height (49.86-50.20), number of branches (15.97-16.20), pods per plant (16.81-16.91) and yield (933.56-1011.56 kg per ha).  Therefore, the application of 2% Zn and 1% Fe is recommended to get a higher yield of chickpea.
Keywords: Foliar spray; chickpea; growth; micronutrients; chlorophyll